A sequência formativa como dispositivo dialógico para a formação continuada de professores na perspectiva da linguística aplicada - Bastos, Rafael Lira Gomes (2023)
Inserted in the community of practice of Applied Linguistics that studies the relationship between language and teaching, this thesis aimed to analyze the role of the Formative Sequence (FS) as a dialogical device for the continuing education of teachers. This general objective unfolded into three specific objectives: (i) to characterize the teaching activity developed at CCI Jóquei through discursive interactions in and about work, (ii) to examine the tensions about teaching activity in the utterences of teachers in a situation of self-confrontation and (iii) to evaluate the application of the Formative Sequence as a device for the continuing education of in-service teachers. The research assumes, theoretically, the dialogical thinking of Bakhtin and the Circle (BAKHTIN, 1997, 2015, 2016, 2017a, 2017b, 2018; VOLÓCHINOV, 1976, 2018) to interpret how human beings act in the world of work via language. This action is also explained in interface with the work concept of the Clinic of Activity (CLOT, 2007, 2010; CLOT; FAÏTA, 2016). Methodologically, we proposed carried out the FS (BASTOS; RIBEIRO, 2019), developed from the indirect method of self-confrontation research. To this end, two simple self-confrontation sessions were held with the CCI Jockey teachers, one cross self-confrontation session, a return to the collective meeting, a continuing education course in three modules and, finally, the writing of a report. The discursive interactions were interpreted from the theoretical-methodological contribution of the Dialogic Discourse Analysis, considering, in general, the dialogic relations between the previous and subsequent utterances, considering an analysis scheme of the development of the genre of activity. Furthermore, we consider the exotopic and chronotopic specificities in the interpretation of interactions in self-confrontation. The analysis of the reports took into account, specifically, the appreciative tones of the teachers about the research. The results indicate that the teaching activity in the context of the CCI Jockey was characterized, to some extent, as demanding due to the infrequency and the number of students per class, in dialogue with the exhaustive routine of the teachers. Among the tensions that stood out, we point out the binomial dynamic/monotonous class, control/non-control of activity time and the use/non-use of the mother tongue as central elements for evaluating the effectiveness of teaching activities. The analysis of the interactions in the continuing education course and the reports point to a positive evaluation of the FS, with emphasis on its potential to promote reflections linked to classroom practices. We conclude that the continuing education favored the emergence of a space-time of reflection, conducive to the emergence of new variants of the activity genre, developing the power to act of the teachers. The FS, therefore, contributed to the strengthening of that collective of work and can even serve as a continuing education device for other contexts, inside and outside the school.